2012
DOI: 10.1103/physrevb.85.165442
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale model for the contact resistance of the nickel-graphene interface

Abstract: We perform first-principles calculations of electron transport across a nickel-graphene interface. Four different geometries are considered, where the contact area, graphene and nickel surface orientations, and the passivation of the terminating graphene edge are varied. We find covalent bond formation between the graphene layer and the nickel surface, in agreement with other theoretical studies. We calculate the energy-dependent electron transmission for the four systems and find that the systems have very si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 20 publications
6
48
0
Order By: Relevance
“…A cutting-edge methodology in the modeling of van der Waals hetero-structures and vdW-TFETs is the employment of ab initio methods to calculate directly the transmission across the physical structures [174], which is a capability that has become available even in some popular, open-source programs such as Quantum Espresso and Siesta [166,175].…”
Section: Physical Mechanisms and Modeling Methodologies For Van Der Wmentioning
confidence: 99%
“…A cutting-edge methodology in the modeling of van der Waals hetero-structures and vdW-TFETs is the employment of ab initio methods to calculate directly the transmission across the physical structures [174], which is a capability that has become available even in some popular, open-source programs such as Quantum Espresso and Siesta [166,175].…”
Section: Physical Mechanisms and Modeling Methodologies For Van Der Wmentioning
confidence: 99%
“…Furthermore, the surface structure of the carbon was a graphene in which the  electrons were delocalized. Based on the close interaction between the carbon and nickel atoms, the  electrons in Pz orbitals of the carbon could become hybridized with the d electrons of the nickel, leading to an increase in the electron mobility [20][21][22], which may result in the nickel bearing a negative charge.…”
mentioning
confidence: 99%
“…As reported in the previous works [9,16], the current density is expected to depend on the contact area: In the case of Cu electrode [18], transmission spectra shift downward in energy with respect to the Fermi level due to the enhancement of electron transfer from the metal surface to the graphene with increasing the contact area. By the analogy with the Cu electrode, thus, the electron transfer from the graphene to the metal surface is expected to increase with increasing the contact area.…”
Section: IIImentioning
confidence: 88%
“…As well as the high contact resistivity, resistance has also been experimentally reported to depend on the metal species [9][10][11] and the process conditions [12]. Several theoretical studies reported geometries, electronic structures [13][14][15], and transport properties [16][17][18] of interfaces between graphene and metal surfaces. Although these theoretical works revealed that the * Corresponding author: jippo.hideyuki@jp.fujitsu.com transport properties depend on the detailed atomic arrangements of GNRs with a few nm width, little is known about the transport properties of GNRs with over 10 nm width.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation